Mindful parenting in Tafsīr al-Taḥrīr wa al-Tanwīr: Reconstructing contemporary Islamic parenting through Qur'anic exegesis - Avina Amalia Mustaghfiroh (Mishkat: Journal of Theology and Civilization, 2026)
Social changes characterized by digitalization, individualization, and shifting values demand adaptive parenting approaches; however, mindful parenting studies remain predominantly grounded in psychology and have not been reconstructed through Tafsīr al-Taḥrīr wa al-Tanwīr. This study aims to reconstruct the concept of mindful parenting from the perspective of Tafsīr al-Taḥrīr wa al-Tanwīr and examine its relevance in addressing contemporary parenting challenges. A qualitative approach employing the thematic (mawḍū‘ī) interpretation method was applied to Q.S. al-Nisāʾ [4]:9, Q.S. al-Taḥrīm [66]:6, and Q.S. Luqmān [31]:13, 16, and 17 based on the exegesis of Muhammad al-Tahir Ibn ‘Ashur. The findings identify five core principles: future-oriented awareness, parental responsibility, spiritual foundation, self-regulation, and character formation. These principles formulate a Contemporary Islamic Parenting model that integrates Qur’anic values with mindful parenting theory, thereby extending Islamic parenting scholarship through a Qur’anic exegetical approach relevant to contemporary social dynamics. Abstrak Perubahan sosial yang ditandai oleh digitalisasi, individualisasi, dan pergeseran nilai menuntut pendekatan pengasuhan yang adaptif, tetapi kajian mindful parenting masih didominasi perspektif psikologi dan belum direkonstruksi melalui Tafsīr al-Taḥrīr wa al-Tanwīr. Penelitian ini bertujuan merekonstruksi konsep mindful parenting dalam perspektif Tafsīr al-Taḥrīr wa al-Tanwīr serta menganalisis relevansinya dalam menjawab tantangan pengasuhan kontemporer. Penelitian menggunakan pendekatan kualitatif dengan metode tafsir tematik (tafsīr mawḍū‘ī) terhadap Q.S. al-Nisāʾ [4]:9, Q.S. al-Taḥrīm [66]:6, serta Q.S. Luqmān [31]:13, 16, dan 17 melalui penafsiran Muhammad al-Tahir Ibn ‘Ashur. Hasil penelitian menunjukkan lima prinsip utama, yaitu future-oriented awareness, parental responsibility, spiritual foundation, self-regulation, dan character formation. Kelima prinsip tersebut membentuk model Contemporary Islamic Parenting yang mengintegrasikan nilai-nilai Qur’ani dengan teori mindful parenting, sehingga memperluas kajian pengasuhan Islam melalui pendekatan tafsir yang relevan dengan dinamika masyarakat kontemporer.